Answer:
c) x=1.23
Explanation:
a =3
b=2
c=-7
use quadratic equation where
![{ ax}^(2) + bx + c = 0 = \frac{ - b \: + or \: - \sqrt{ {b} ^(2) - 4ac} }{2a}](https://img.qammunity.org/2022/formulas/mathematics/high-school/gedinjhug9ba9os823wq53mwnnz6ijq8g3.png)
-2+/- square root of (2^2- (4×3×-7) ) all that over 2x3
square root of (2^2-(4×3×-7) )
= 9.38083152
2×3=6
-2+or - 9.38 all that divided by 6
-2+9.38= 7.38÷6
x=1.23
or
-2-9.38 all divided by 6
-2-9.38= -11.38 ÷6
x= -1.9
all in all x can't be negative meaning x=1.23